The ambiguity challenge: Why the world needs a multilateral nuclear cruise missile agreement. (4th May 2017) - Parthemore, Christine
ABSTRACT: The US long-range standoff (LRSO) weapon program is clearly a major factor in the worldwide trend toward fielding nuclear-armed cruise missiles. Public information shows that it will likely have new abilities beyond its predecessor air-launched cruise missile, and these potential properties, and the fact that the Air Force intends to field it on its new stealth bomber, may raise new concerns among potential adversaries and alter strategic calculations. The US nuclear modernization plan, as of this writing, includes replacing the existing stock of 575 air-launched cruise missiles with around 1000 LRSO weapons. The concerns surrounding the LRSO are feeding the emergence of a serious debate in the United States over its future, and whether a move to end the program could help tilt other countries away from nuclear-armed cruise missiles.